The Turnover of Cholesterol in Human Atherosclerotic Arteries - Jagannathan, S. N. (1974)
The equilibration of cholesterol between plasma and atherosclerotic arteries was studied in 13 patients with obstructive atherosclerosis 2-96 days after the intravenous and/or oral administration of isotopic cholesterol. Arterial specimens were obtained in 12 patients during surgery for arterial reconstruction and in a 13th patient at autopsy. Equilibration was calculated as the specific radioactivity of cholesterol in the arterial tissue relative to that in the plasma (percent). In specimens obtained 2-4 days after pulse labeling, the specific activity of cholesterol in atheroma ranged from 0.3 to 4.5% of that in the plasma. By 17-27 days, the relative specific activity ranged from 6 to 20% in different arteries. In contrast, cholesterol of skeletal muscle had a relative specific activity of 96% by 22 days. By 61-96 days, atheroma cholesterol in the abdominal aorta, common iliac, and femoral arteries had equilibrated to 55, 30, and 26%, respectively. In the patient who died at 96 days, the cholesterol in the coronary arteries had a mean equilibration of 66%, similar to the values for the abdominal (66%) and thoracic (57%) aortas. The route of administration of the isotope did not influence the equilibration. Within the atheromatous plaque, the superficial layers equilibrated better than the deeper layers (75% vs. 22%). The free cholesterol in the atheroma equilibrated to a significantly higher extent than did esterified cholesterol (59% vs. 38%). There was a fourfold higher specific activity of cholesterol in the media than in the corresponding intima (916 vs. 230 dpm/mg). The estimated minimal influx rates of plasma cholesterol into the atheromatous intima ranged from 0.065 to 0.274 mg of cholesterol/g dry tissue per day for different arteries. The approximated turnover times of atheroma cholesterol ranged from 442 days for the abdominal aorta and the coronary arteries to 580 days for the common iliac and 821 and 934 days, respectively, for the femoral and the carotid arteries. These data indicate a definite, though slow, exchange of cholesterol between the plasma and severely atherosclerotic human arteries. Within the atheroma, there are multiple pools of cholesterol, each turning over differently and more slowly than the cholesterol of most other tissues, such as the skeletal muscle. The estimates of influx rate and turnover time of atheroma cholesterol suggest the possibility that this cholesterol is mobilizable, an indication of potential regression of atheromatous lesions in man.